The Influence of Group Leadership, Groupthink, and Tacit Knowledege in Group Decision Making: Case Groups Supervised by KSPPS Baytul Ikhtiar - Zahara, Aisyah; Sarwoprasodjo, Sarwititi; Hamzah, Hamzah (Departemen Sains Komunikasi dan Pengembangan Masyarakat, Fakultas Ekologi Manusia, IPB, 2017)
Desicion making is the process of choosing alternative among several alternatives and canÂ be influence by many factors. Decision making can be happen on individual situation or group situation. The purposes of this research are: (1) to analyze the influence of group leadership on group decision making, (2) to analyze the influence of groupthink on group decision making, and (3) to analyze the influence of tacit knowledge on group decision making.Â This is an explanatory research using quantitaive approach supported by qualitative data with the total of respondents 30 groups. The subject of this research are the groups under supervise BMT Koperasi Baytul Ikhtiar (BAIK) located in Kecamatan Ciampea, Kabupaten Bogor. The technique analysis using regression test. The results of this research shows that there are a negative influence between groupthink on group decision making. Also there are a positive influence between tacit knowledge on group decision making.Keywords : groupthink, group leadership, group decision making, tacit knowledge===================================================ABSTRAKPengambilan keputusan adalah proses pemilihan alternatif dari berbagai alternatif-alternatif yang ada dan dipengaruhi berbagai faktor. Pengambilan keputusan dapat terjadi pada individu maupun kelompok. Tujuan penelitian ini adalah untuk: (1) menganalisis pengaruh kepemimpinan kelompok terhadap pengambilan keputusan, (2) menganalisis pengaruh groupthink terhadap pengambilan keputusan, dan (3) menganalisis pengaruh pengetahuan tacit terhadap pengambilan keputusan. Jenis penelitian ini adalah explanatory serta menggunakan pendekatan kuantitatif yang didukung oleh data kualitatif dengan responden sebanyak 30 kelompok. Subjek penelitian ini adalah kelompok-kelompok binaan BMT Koperasi Baytul Ikhtiar (BAIK) yang berlokasi di Kecamatan Ciampea, Kabupaten Bogor. Teknik analisis yang digunakan adalah uji regresi. Hasil penelitian menunjukkan bahwa terdapat pengaruh negatif groupthink terhadap pengambilan keputusan. Lalu terdapat pengaruh positif pengetahuan tacit terhadap pengambilan keputusan.Kata Kunci : groupthink, kepemimpinan kelompok, pengambilan keputusan kelompok, pengetahuan tacit